Green growth in NDN: Deployment of content stores - Aubry, Elian; Silverston, Thomas; Chrisment, Isabelle (Proceedings of the ... IEEE Workshop on Local and Metropolitan Area Networks, 2016)
Named-Data Networking architecture relies on cache networks, where nodes store the data for further requests. However, the memory needed at each node called Content Store represents the most significant part of the entire cost of the infrastructure that has to be supported by network providers, making difficult the change from the current Internet infrastructure to a Future Internet based on NDN. Thus, a legitimate question would be: "are all these Content Stores useful in a large-scale NDN network?" In this paper, we investigate the impact of Content Stores in NDN network, and we evaluate the performances of the NDN architecture according to the number of Content Stores effectively deployed in the network. We show through extensive simulation experiments in NS-3 that only about 50% of nodes with Content Stores is enough to achieve higher level of performances than a fully-deployed NDN network. This result is very important for the deployment of NDN architecture as it shows that the infrastructure cost can be drastically reduced and it is an incentive for network providers that benefits directly from this result.